RANCANG BANGUN TIMBANGAN DIGITAL DENGAN FASILITAS KLASIFIKASI INDEKS MASSA TUBUH MENGGUNAKAN ALGORITMA LOGIKA FUZZY - Nurroqim, Alfian; Musafa, Akhmad (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
In general, there is already a way to calculate the value of Body Mass Index (BMI). But the determination in this way is very rigid, because if there is a small difference in value it can result in differences in BMI status. Using fuzzy logic can give tolerance to the BMI value, so that if there is a small change it will not cause a significant difference in BMI status. In this final project, a digital scale is designed which is equipped with facilities for determining BMI using the Mamdani fuzzy logic algorithm based on the results of measurements of height and weight. Measurement of height using an ultrasonic sensor while measurement of weight using a load cell sensor. The input height and weight from sensor readings will be fuzzified into linguistic variables using a membership function, and fuzzy output in the form of BMI values ​​which are fuzzified into firm values ​​using linguistic variables from the input membership function. The implication function is performed using the MIN function and the rule composition using the MAX function. The fuzzy BMI is defuzzified using the center of gravity method. System testing was carried out using 7 data samples with a height of 50 cm to 200 cm and a weight of 10 kg to 120 kg. In this system, the BMI value is not only displayed on the LCD but also in the form of sound using speakers. The test results show that there are differences with the results of BMI calculations using firm logic as a reference, overall there is an average error of BMI results using firm logic with fuzzy logic of 19.35%.